Analysis of Learning Barriers and Elementary School Students' Errors in Solving Mathematical Story Problems - Luthfiatunnisa, Ranti; Hardi, Hardi (UIN Raden Mas Said Surakarta, 2024)
The errors made by students can be used as a benchmark for students' understanding of the material. This study aims to determine the obstacles to students' learning in solving mathematical story problems based on Brousseau & Balacheff's theory, to find out students' errors in solving mathematical story problems based on Newman's Error Analysis theory, and the factors that cause students to make mistakes in solving mathematical story problems. This research was conducted at MI GUPPI Wironanggan from September 2023 to March 2024. The subjects of this study were grade V students. The type of research is qualitative. Data collection used semi-structured interviews and observations. This study uses supporting instruments like mathematical story problems on speed and discharge material. The data analysis technique uses source triangulation and technique triangulation. The results of this study are the existence of learning obstacles experienced by students, including Ontogenic Obstacles, Didactic Obstacles, and Epistemological Obstacles; the errors made by students include errors in reading, understanding, transforming, and concluding. Several factors that cause student errors include low accuracy in solving problems, not memorizing formulas and not understanding their use, and low student ability in performing arithmetic operations. Based on the study results, teachers are expected to increase the intensity of giving varied questions at various levels